A MUTYH germline mutation is associated with small intestinal neuroendocrine tumors. Issue 8 (August 2017) - Dumanski, Jan P; Rasi, Chiara; Björklund, Peyman; Davies, Hanna; Ali, Abir S; Grönberg, Malin; Welin, Staffan; Sorbye, Halfdan; Grønbæk, Henning; Cunningham, Janet L; Forsberg, Lars A; Lind, Lars; et al.
Abstract : The genetics behind predisposition to small intestinal neuroendocrine tumors (SI-NETs) is largely unknown, but there is growing awareness of a familial form of the disease. We aimed to identify germline mutations involved in the carcinogenesis of SI-NETs. The strategy included next-generation sequencing of exome- and/or whole-genome of blood DNA, and in selected cases, tumor DNA, from 24 patients from 15 families with the history of SI-NETs. We identified seven candidate mutations in six genes that were further studied using 215 sporadic SI-NET patients. The result was compared with the frequency of the candidate mutations in three control cohorts with a total of 35, 688 subjects. A heterozygous variant causing an amino acid substitution p.(Gly396Asp) in the MutY DNA glycosylase gene ( MUTYH ) was significantly enriched in SI-NET patients (minor allele frequencies 0.013 and 0.003 for patients and controls respectively) and resulted in odds ratio of 5.09 (95% confidence interval 1.56–14.74; P value = 0.0038). We also found a statistically significant difference in age at diagnosis between familial and sporadic SI-NETs. MUTYH is involved in the protection of DNA from mutations caused by oxidative stress. The inactivation of this gene leads to specific increase of G:C- > T:A transversions in DNA sequence and has been shown to cause various cancers in humans and experimental animals. Our results suggest that p.(Gly396Asp) in MUTYH, and potentially other mutations in additional members of the same DNA excision-repair pathway (such as the OGG1 gene) might be involved in driving the tumorigenesis leading to familial and sporadic SI-NETs.